Philosophy of Islamic Education in the Trajectory of Time: Efforts to Formulate Reflective and Contextual Islamic Education - St. Fatimah K; Moh. Yahya Obaid (Dirasah: Jurnal Pendidikan Islam, 2025)
This study aims to examine the philosophy of Islamic Religious Education (PAI) in the historical trajectory as the basis for the formulation of reflective and contextual Islamic education. The background of this study departs from the fact that the current practice of Islamic education is still dominated by normative and textualistic approaches, which are less able to answer the complexity of modern life. Meanwhile, Islamic philosophical thought from various historical phases holds rich conceptual potential to form a more critical, adaptive and humanistic educational model. This research uses a qualitative approach with a library research method, as well as philosophical-historical analysis of the works of Islamic thinkers from classical, modern, to contemporary times. The results of the study found that the philosophy of PAI underwent a significant evolution of thought in line with the social and intellectual changes of Muslims. There are five main principles that were successfully synthesized from the trajectory of thought: (1) integration of reason and revelation, (2) spirituality and ethics as the foundation of education, (3) historical and contextual awareness, (4) critical attitude towards tradition and openness to innovation, and (5) responsibility for global and humanitarian issues. These principles form the framework of Islamic education philosophy that is not only normative, but also transformative and dialogical with the times. The findings indicate that the philosophy of Islamic education, if explored deeply, can be a conceptual foundation in reforming the current curriculum and methodology of Islamic education. The limitations of this study lie in the limited scope of sources and do not include empirical data, so further research is needed that tests these principles in real educational practices in various social contexts.